Microstructural failure in Ge2Sb2Te5 phase change memory cell - Kim, Yong Tae; Kim, Young Hwan (WILEY-V C H VERLAG GMBH, 2014)
The microstructural behavior of a Ge2Sb2Te5 (GST) film in a phase change memory cell has been investigated by high-resolution transmission electron microscopy (HR-TEM). The HR-TEM results indicate that both hexagonal structured GeSbTe (GST) and metastable GeTe phases appeared in the amorphous GST film after about 10(3)cycles of set/reset operations. These hexagonal GST grains, although the grain size is very small, are relatively not easily changed into the amorphous phase compared with the fcc GST, which results in an imperfect phase transformation during the quenching process of the reset cycle. Voids are formed at the interface close to the top electrode and the formation of the voids widens the GST film during the multiple cycles of set/reset operations. These experimental results may explain the failure mechanism of the GST memory cell. (C) 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: MECHANISM